2010
DOI: 10.1089/mdr.2009.0132
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Extended-Spectrum β-Lactamases Produced byEscherichia coliIsolated from Hospitalized and Nonhospitalized Patients: Emergence of CTX-M-15-Producing Strains Causing Urinary Tract Infections

Abstract: Extended-spectrum b-lactamase (ESBL)-producing Escherichia coli isolates were obtained from hospitalized and nonhospitalized patients in Belgium between August 2006 and November 2007. The antimicrobial susceptibility of these isolates was determined and their ESBL genes were characterized. Clonal relationships between the CTX-Mproducing E. coli isolates causing urinary tract infections were also studied. A total of 90 hospital-and 45 community-acquired cephalosporin-resistant E. coli isolates were obtained. Te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
45
1
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(54 citation statements)
references
References 20 publications
5
45
1
3
Order By: Relevance
“…The bla CTX-M-1 gene was carried by a 100-kb IncI1/ST3 plasmid, as detected with S1 nuclease treatment of DNA followed by pulsed-field gel electrophoresis (PFGE), Southern blot hybridizations with adequate digoxigenin (DIG)-labeled probes (Roche Applied Science, Mannheim, Germany), PCRbased replicon typing (Diatheva, Fano, Italy), and plasmid multilocus sequence typing (MLST) (5). The restriction fragment length polymorphism (RFLP) profile of the IncI1/ST3 plasmid after digestion with PstI or EcoRI was comparable but nonidentical to those of previously published bla CTX-M-1 IncI/ , an ST that has been observed previously in both humans and animals (7,8).…”
supporting
confidence: 76%
“…The bla CTX-M-1 gene was carried by a 100-kb IncI1/ST3 plasmid, as detected with S1 nuclease treatment of DNA followed by pulsed-field gel electrophoresis (PFGE), Southern blot hybridizations with adequate digoxigenin (DIG)-labeled probes (Roche Applied Science, Mannheim, Germany), PCRbased replicon typing (Diatheva, Fano, Italy), and plasmid multilocus sequence typing (MLST) (5). The restriction fragment length polymorphism (RFLP) profile of the IncI1/ST3 plasmid after digestion with PstI or EcoRI was comparable but nonidentical to those of previously published bla CTX-M-1 IncI/ , an ST that has been observed previously in both humans and animals (7,8).…”
supporting
confidence: 76%
“…The CTX-M-15-type ESBL-producing E. coli ST131 clone has spread across many regions of the world (28)(29)(30)(31). Our data showed that the CTX-M-15-type comprised 84 of the strains, including some strains with a combination CTX-M-15 and TEM-1 or SHV-7.…”
Section: Discussionmentioning
confidence: 69%
“…ESBL-producing strain ST617 has also spread worldwide (28,29,39,40) and can be found, for instance, in Belgium, Sweden, Nigeria, and France. Our MLST data showed that, although 24 of the ESBL-producing strains were non-typable, ST617 was commonly found in our ESBL isolates, as in the aforementioned studies; ST617 strains had higher resistance to most of the antibiotics tested in this study, except IPM, AMK, and FOM.…”
Section: Discussionmentioning
confidence: 99%
“…ST131 is prevalent in most parts of the world, and is often associated with fluoroquinolone resistance and the production of CTX-M-15. ST405 with various types of CTX-M b-lactamases also has a worldwide distribution but is not as prevalent as ST131 (Coque et al, 2008;Jones et al, 2008;Mihaila et al, 2010;Smet et al, 2010). These reports suggest that the intercontinental dissemination of ST131, and to a lesser extent ST405, has in part contributed to the worldwide emergence of CTX-M-producing E. coli.…”
Section: Introductionmentioning
confidence: 99%